CIPTA LAGU ANAK WARNA WARNI SEBAGAI MEDIA EDUKASI ESTETIKA DAN APRESIASI ALAM UNTUK USIA DINI - Nur Indriani; Anisa Safitri; Ameliya; Irmalasari; Nurdamayanti; Khusnal Hawa Tiwi; Ftri Hijratunnisah; Wuwun; Abdul Afan Gafar; Roy Martin; Irmaningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the decreasing number of children's songs with educational and aesthetic value, while young children are more familiar with popular adult songs that are less relevant to their world. This condition creates a need for musical works that can foster sensitivity, appreciation of nature, and aesthetic values ​​from an early age. The purpose of this research is to create a children's song entitled "Colors of the World" as a learning medium that connects children with nature through a fun and meaningful musical experience. The research uses a creation method that emphasizes the creative process as a form of scientific and artistic exploration, through the stages of conceptual observation, musical design, lyric and melody creation, implementation, and evaluation of the work. The results show that the song "Colors of the World" successfully presents a holistic learning experience by combining educational, aesthetic, and interactive elements. Simple lyrics, cheerful rhythms, and elements of movement and handclaps can increase children's enthusiasm, strengthen language, motor, and social-emotional skills, and foster a sense of awe and gratitude for the beauty of God's creation.